Organization Development Values From a Future-Oriented Perspective: An International Delphi Study. (September 2021) - Yoon, Hyung Joon; Farley, Sasha B.; Padilla, Cesar
This study sought to identify Organization Development (OD) values to guide OD practitioners using a future-oriented perspective to differentiate OD from related fields. Employing six guiding principles, a Delphi study with three rounds was conducted with 42 international OD practitioners and researchers who practice in 58 countries collectively. As a result, this study identified nine OD values ( awareness of self and system, continuous learning and innovation, integrity, courageous leadership, trust and respect, diversity, collaborative engagement, strategic practicality, and client growth and development) along with 71 corresponding behavioral indicators. This article compares the identified values with OD values featured in the existing literature, adding temporal external validity and highlighting the consistency of OD values over time. Also discussed are the implications of this research for OD practitioners, the OD field, OD researchers, and other groups.